Research-based teaching and learning - Navarro, Rosita L.; Santos, Rosita G. (Cubao, Philippines : Lorimar Publishing Company Inc., 2011)
This book tackles the concern that teaching ought to be based on research evidence to encourage more practicing teachers to do research in the likelihood that the research results would enhance their own peace.
The role of Research in Teaching and in Ensuring Learning Outcomes 1 -- Research Methods and Techniques in ensuring Teaching and Learning Outcomes 20 -- The Use of Statistics in Research-Based Teaching and Learning 32 -- The Elements of the Research Proposals 51.
Includes bibliographical references.
Keywords: EFFECTIVE TEACHING